Analysis of Science Process Skills towards Teacher Professionalism in Islamic Elementary School - Irham Nugroho; Akhmad Baihaqi; Muis Sad Iman; Tohirin Tohirin (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
In fact, the success of the learning implementation process at SD / MI still relies on classroom teachers. So that absolutely has not provided the opportunity for students to develop independently through the process skills they have acquired. One of the successes of learning is reflected in the science process skills that the teacher implements to construct students' understanding. Science process skills are closely related to teacher professionalism. The purpose of this study was to analyze the relationship between science process skills and teacher professionalism in SD / MI. This research uses descriptive quantitative method. Data were collected through observation, group discussions and field assessments by distributing questionnaires. The results of this study indicate that the analysis of science process skills on teacher professionalism shows a good category. However, this good category is measured based on the average score of all aspects of science process skills on teacher professionalism. The correlation between science process skills and teacher professionalism is shown in the indicator of science process skills observing and inferring to professional competence, where when science process skills in observing aspects and inference show a percentage of 71.5%, it will have an impact on professional competence which shows a percentage of 71%, it means that science process skills are closely related to teacher professionalism. In addition, indicators of science process skills such as classification, interpreting, predicting, and communicating in good categories have an impact on teacher professional competence with pedagogic, personality and social indicators. This shows that teachers with good science poses skills will show teacher professionalism.